PENGGUNAAN DATA PENGINDERAAN JAUH DALAM ANALISIS BENTUKAN LAHAN ASAL PROSES FLUVIAL DI WILAYAH KARANGSAMBUNG - Raharjo, Puguh Dwi (Universitas Negeri Semarang, 2013)
Geomorphology object study is land form which composed in earth surfaceweither in the land or in the bottom of the sea. Geomorphological condition of aregion is a natural resource. A part of it is land resource. Land resource optimalutilization is a must to get an optimal result. Using remote sensing image, it couldbe analyze the connection of land form. The aim of this research was to analyzeland form of fluvial process in Karangsambung area using satellite imagery. Thisresearch’s result showed that land sub-form of fluvial process consist of fivekinds, i.e.: inundation land, meander river, woven river, pothole, point bar anddead river.